VitisCyc: a metabolic pathway knowledgebase for grapevine (Vitis vinifera) - Naithani, Sushma; Raja, Rajani; Waddell, Elijah N.; Elser, Justin; Gouthu, Satyanarayana; Deluc, Laurent G.; Jaiswal, Pankaj (Frontiers in Plant Science, 2014)
We have developed VitisCyc, a grapevine-specific metabolic pathway database that allows researchers to i) search and browse the database for its various components such as metabolic pathways, reactions, compounds, genes and proteins, ii) compare grapevine metabolic networks with other publicly available plant metabolic networks, and iii) upload, visualize and analyze high-throughput data such as transcriptomes, proteomes, metabolomes etc. using OMICs-Viewer tool. VitisCyc is based on the genome sequence of the nearly homozygous genotype PN40024 of Vitis vinifera ‘Pinot Noir’ cultivar with 12X v1 annotations and was built on BioCyc platform using Pathway Tools software and MetaCyc reference database. Furthermore, VitisCyc was enriched for plant-specific pathways and grape-specific metabolites, reactions and pathways. Currently VitisCyc harbors 68 super pathways, 362 biosynthesis pathways, 118 catabolic pathways, 5 detoxification pathways, 36 energy related and 6 transport pathways, 10,908 enzymes, 2912 enzymatic reactions, 31 transport reactions and 2,024 compounds. VitisCyc, as a community resource, can aid in the discovery of candidate genes and pathways that are regulated during plant growth and development, and in response to biotic and abiotic stress signals generated from a plant’s immediate environment. VitisCyc version 3.18 is available online at http://pathways.cgrb.oregonstate.edu.